Intussusception as an acute abdomen caused by non Hodgkins lymphoma: A rare case (International Journal of Biomedical and Advance Research, 2015)
In children, non-Hodgkins lymphoma has been found to be the lead point in intussusception involving the terminal ileum. We present here a case of ileal primary non-Hodgkins lymphoma which presented as intussusception, highlighting the presentation of this patient, with a brief review of the literature.